2020
DOI: 10.1080/08824096.2020.1841621
|View full text |Cite
|
Sign up to set email alerts
|

Spousal interference and relational turbulence during the COVID-19 pandemic

Abstract: Relational Turbulence Theory proposes that when romantic partners interrupt everyday routines in response to transitions, affective arousal will be heightened in the form of more intense emotions. The goal of this study was to test this theoretical logic in a married sample of 165 spouses during the initial peak of the COVID-19 pandemic (April, 2020). Participants completed an online survey measuring how often their spouse interfered with their daily routines, the negative emotions they experienced when intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…They also suggest, however, that whereas prior work from non‐Israeli studies have found associations between all relational uncertainty sources and various of outcomes during COVID‐19 (e.g., Jones & Theiss, 2021 ; Lillie et al., 2021 ), in our Israeli sample each source of relational uncertainty diverged in its association with different facets of distress. A similar trend was found with regard to couple interdependence where, contrary to US‐based studies (Goodboy et al., 2021 ; Jones & Theiss, 2021 ; Knoster et al., 2020 ), only interference from a partner, but not facilitation, corresponded with psychological distress. It is possible that with the ongoing stress that characterizes the life in Israel both pre‐ and during the pandemic (Hobfoll et al., 2009 ; Pat‐Horenczyk & Schiff, 2019 ), Israeli couples' accumulated tension has led them to focus more on the negative, rather the positive facets of couple interdependence, noticing interruptions from partners more than assistance from them.…”
Section: The Israeli Contextsupporting
confidence: 68%
“…They also suggest, however, that whereas prior work from non‐Israeli studies have found associations between all relational uncertainty sources and various of outcomes during COVID‐19 (e.g., Jones & Theiss, 2021 ; Lillie et al., 2021 ), in our Israeli sample each source of relational uncertainty diverged in its association with different facets of distress. A similar trend was found with regard to couple interdependence where, contrary to US‐based studies (Goodboy et al., 2021 ; Jones & Theiss, 2021 ; Knoster et al., 2020 ), only interference from a partner, but not facilitation, corresponded with psychological distress. It is possible that with the ongoing stress that characterizes the life in Israel both pre‐ and during the pandemic (Hobfoll et al., 2009 ; Pat‐Horenczyk & Schiff, 2019 ), Israeli couples' accumulated tension has led them to focus more on the negative, rather the positive facets of couple interdependence, noticing interruptions from partners more than assistance from them.…”
Section: The Israeli Contextsupporting
confidence: 68%
“…It is likely that a different pattern of results would emerge for married or cohabitating couples with regard to interdependence processes, for whom it is unlikely that both partner facilitation and interference would decrease during this extended time of social distancing, working remotely, homeschooling children, etc. For married and cohabitating couples, interdependence processes are expected to play a stronger role in the experience of relational turbulence during a pandemic (Knoster et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the negative side, stress was related to lower relational satisfaction only for the women with higher socioeconomic status, but not for those with lower socioeconomic status or for men [38]. Negative emotions and relational turbulence increased from before the pandemic to during the pandemic due to a decrease in partner interdependence and an increase in spousal interference [39,40]. Finally, the illness of a family member was associated with increased fear of COVID-19, anxiety, depression and stress [41] and adverse life events and perceived threat of COVID-19 affected the relational quality of same-sex couples by increasing complaint avoidance [42].…”
Section: Adult Romantic Relationshipsmentioning
confidence: 92%